Tatak Pilipino [episode no. 38] ([Quezon City ABS-CBN], 1991)
A unique display of Pilipino ways and style.
Male wearing earrings (15 min.) -- Menstruation feature (15 min.) -- Sa Kabilang Banda featuring Regine Velasquez and her art work (10 min.) -- Simbahang kalikasan (5 min.) -- Balagtasan feature on U.S. military bases (15 min.).
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Velasquez, Regine; Immaculate Parish Church (Las Pinas, Manila).; Menstruation -- Folklore; Balagtasan; Earrings -- Philippines; Grooming for men; Military bases, American